Case Report: A rare case of primary paraganglioma of the gallbladder with a literature review - Xia, Yijun; Wang, Shi; Wang, Xidong; Du, Jiya; Zhang, Lei; Xia, Long (Frontiers in Oncology, 2023)
Introduction: Paragangliomas of the gallbladder are exceptionally rare. To date, only few cases of this disease had been reported globally, and majority were found incidentally during surgery. Although complete resection can achieve a curative effect, specific targeted drugs may have survival benefits for patients with potential recurrence and metastasis risks. Case presentation: A 48-year-old woman was scheduled for anatomical central hepatectomy due to the discovery of a liver mass. Surprisingly, it was found that the gallbladder tumor was accompanied by intrahepatic invasion rather than primary liver lesions during the operation. Postoperatively, the lesion was confirmed to be a paraganglioma originating from the gallbladder with intrahepatic invasion on histopathology. After surgery, the patient was treated with a new targeted drug, Surufatinib (200mg, qd), and no recurrence was observed during regular follow-up. Discussion: Gallbladder paraganglioma was rare and occult, and surgeons do not know it well, so it was easily to be misdiagnosed before surgery. Postoperative pathological examination was the gold standard for diagnosis. Conclusion: Given the tumors contained abundant blood sinuses, the early and continuous enhancement of dynamic enhanced CT scanning was its characteristic manifestation. We presented a case in which a primary gallbladder paraganglioma was identified incidentally in a patient who was misdiagnosed as a liver lesion before surgery. Based on our experience in this work, the en-bloc resection technique in combination with Surufatinib might have a survival benefit in patient at risk of potential recurrence or metastasis, however, further follow-up observation was also needed.